Expediency of Producing Bioethanol from the Maize Grain - Т. В. Дудка (Plant Varieties Studying and Protection)
The article reflects economical value and origin of maize as an important energy crop. It specifies volumes of bioethanol production worldwide, as well as analyzes legal provisions for the development of alternative power engineering, advantages and shortcomings of bioenergy is general.